An Aerospace Experience at ORBITEC - 2016 WSCG Industry Internship Award - Andryk, Brian Alan (Proceedings of the Wisconsin Space Conference, 2017)
The objective of the 2016 Wisconsin Space Grant Consortium (WSCG) Industry Internship Award is to allow students to gain valuable aerospace involvement through an internship with an industry partner. During my industry partnership with ORBITEC, I experienced the aerospace industry through a variety of projects. Some of these projects include but are not limited to the VEGGIE System, Zero Gravity Mass Measurement Device (ZGMMD), and Plastic Melt Waste Compactor (PMWC). Â My internship opportunity not only gave me important insights into engineering, but it also led to a full time engineering position with the company.